The Impact of Internal, External, and Competitor Factors on Marketing Strategy Performance: A Case Study of Four Scrap Metal Companies in Indonesia - Efendi, Achmad Arif Rachmad; Halim, Rizal Edy (UNIVERSITAS PAKUAN, 2025)
This study analyzes the impact of internal and external factors, as well as competition, on the performance of marketing strategies in Indonesia’s scrap metal industry. This industry plays a crucial role in the circular economy by supplying secondary raw materials to various manufacturing sectors. However, companies in this sector face challenges such as raw material price fluctuations, government regulations, and intense competition from both local and global players. This study employs a quantitative approach using the Structural Unobserved Regression (SUR) method to examine the relationship between key factors affecting the marketing performance of four scrap metal companies in Indonesia. The findings reveal that the average selling price has a positive and significant impact on marketing performance in PT OPMS, PT GDST, and PT GGRP, while global market demand significantly affects PT KRAS. Competitor product variations also positively influence PT GGRP. Conversely, marketing expenditures, interest rates, and competitor prices do not significantly impact most companies. This study confirms that optimizing selling prices, understanding global market demand, and adapting to competitor product variations are key factors in enhancing competitiveness. Therefore, companies must implement flexible pricing strategies, improve operational efficiency, and expand their global market share to address industry challenges.